KONSEP HUKUM KETENAGAKERJAAN DALAM HAL PEMBERIAN SANKSI HUKUM TERHADAP PERUSAHAAN YANG MEMBAYAR UPAH DI BAWAH STANDAR MINIMUM - Dewi Pratiwi, Meirina; Erniwati, Erniwati; Jhoni, Jhoni (Justici, 2023)
Abstract The policy of setting minimum wages within the current framework of wage protection still encounters many obstacles as a result of the non-availability of uniformity of wages, both regionally/provincially or districtly/municipally, and provincially or districtly/municipally sectorally, as well as nationally. In setting the minimum wage there are still differences based on the level of ability, nature and type of work in each company, the conditions are different, in each region. The problem in this paper is how legal sanctions are imposed on companies that pay wages below the minimum standard based on the concept of labor law. This study will use a normative juridical approach. The juridical (normative) approach is mainly aimed at obtaining theoretical matters, namely regarding legal sanctions for companies that pay employees wages below the minimum standard. The conclusion of this paper is the legal sanctions against companies that violate agreements the work is subject to civil law sanctions in which an agreement entered into by the parties in relation to a work agreement may not conflict with laws and regulations, namely in this case the Job Creation Law, PP Wages, and Ministerial Regulations/Decisions. Thus, promising wages below the minimum wage is null and void.